Do contemporary imaging and biopsy techniques reliably identify unilateral prostate cancer? Implications for hemiablation patient selection. Issue 17 (1st May 2019) - Johnson, David C.; Yang, Jason J.; Kwan, Lorna; Barsa, Danielle E.; Mirak, Sohrab A.; Pooli, Aydin; Sadun, Taylor; Jayadevan, Rajiv; Zhou, Steve; Priester, Alan M.; Natarajan, Shyam; Bajgiran, Amirhossein M.; et al.
Abstract : Background: Hemiablation is a less morbid treatment alternative for appropriately selected patients with unilateral prostate cancer (PCa). However, to the authors' knowledge, traditional diagnostic techniques inadequately identify appropriate candidates. In the current study, the authors quantified the accuracy for identifying hemiablation candidates using contemporary diagnostic techniques, including multiparametric magnetic resonance imaging (mpMRI) and MRI‐fusion with complete systematic template biopsy. Methods: A retrospective analysis of patients undergoing MRI and MRI‐fusion prostate biopsy, including full systematic template biopsy, prior to radical prostatectomy in a single tertiary academic institution between June 2010 and February 2018 was performed. Hemiablation candidates had unilateral intermediate‐risk PCa (Gleason score [GS] of 3+4 or 4+3, clinical T classification ≤T2, and prostate‐specific antigen level <20 ng/dL) on MRI‐fusion biopsy and 2) no contralateral highly or very highly suspicious Prostate Imaging Reporting and Data System version 2 (PI‐RADSv2) MRI lesions. Hemiablation candidates were inappropriately selected if pathologists identified contralateral GS ≥3+4 or high‐risk ipsilateral PCa on prostatectomy. The authors tested a range of hemiablation inclusion criteria and performed multivariable analysis of preoperative predictors of undetected contralateral disease. Results: Of 665 patients, 92 met primary hemiablation criteria. Of these 92 patients, 44 (48%) were incorrectly identified due to ipsilateral GS ≥3+4 tumors crossing the midline (21 patients), undetected distinct contralateral GS ≥3+4 tumors (20 patients), and/or ipsilateral high‐risk PCa (3 patients) on prostatectomy. The rate of undetected contralateral disease ranged from 41% to 48% depending on inclusion criteria. On multivariable analysis, men with anterior index tumors were found to be 2.4 times more likely to harbor undetected contralateral GS ≥3+4 PCa compared with men with posterior lesions ( P  < .05). Conclusions: Clinicians and patients must weigh the risk of inadequate oncologic treatment against the functional benefits of hemiablation. Further investigation into methods for improving patient selection for hemiablation is necessary. Abstract : Even with contemporary diagnostic techniques, including magnetic resonance imaging (MRI), MRI‐fusion biopsy, and systematic template biopsy, appropriately identifying unilateral prostate cancer remains difficult. Nearly one‐half of hemiablation candidates based on preoperative radiographic, clinical, and pathologic factors harbored pathology, making them inappropriate for hemiablation in their radical prostatectomy specimen.